Checklist of Protozoan parasites of fishes from Brazil - Eiras, Jorge C.; Takemoto, Ricardo M.; Pavanelli, Gilberto C.; Luque, José L. (Zootaxa, 2012)
Provided is a list of the protozoan parasites of freshwater and marine fishes from Brazil. This report includes informationabout the site of infection, host habitat, localities and references of 100 parasite species (1 amoeba, 70 flagellates, 13 api-complexa and 16 ciliates) distributed among 112 different host species, mainly from freshwater. It is concluded that thediversity of protozoan parasites from Brazilian fish is understudied, and it is suggested that appropriate measures be taken in the research efforts to increase studies on the diversity of Protozoans parasites of fish from Brazil.